Analysis of Postcolonialism In The Short Story "Lilin" By Sunaryono Basuki KS - Afidha Anhar*; Novita Dewi (Riwayat: Educational Journal of History and Humanities, 2024)
This research aims to find out and describe the concepts in the theory or study of postcolonialism contained in the data source in the form of a short story Lilin by Sunaryono Basuki KS. This research is a descriptive qualitative research with data collection techniques using listening and recording techniques. The data of this research is in the form of sentence quotations in the short story "Lilin" that show the use of concepts or representations of postcolonialism theory. The results in this study include (1) the paradigm of Western superiority to the East and (2) the concept of mimicry.